The Impact of Artificial Intelligence (AI) Implementation on the Labor Market from the Perspective of Maqashid Syariah - Kurratu A'yuni; Fahrurrozi (UIN Sunan Kalijaga Yogyakarta, 2025)
Research Aims: This study aims to analyze the impact of AI implementation on the labor market by integrating the Maqashid Syariah perspective as an ethical framework. Methodology: This research employed a qualitative approach with library research methods. Data was collected from journals, books, research reports, and academic publications. Analysis was conducted using content analysis through data reduction, presentation, and drawing conclusions. Research Findings: The implementation of AI has three main effects on the labor market: (1) productivity effect, namely increased efficiency, productivity, and work safety, (2) replacement effect, namely the shift in human roles due to automation, especially in routine work, and (3) recovery effect, namely the creation of new jobs that require high skills and digital competencies. AI increases productivity and opens up new job opportunities, but also raises challenges such as structural unemployment, skills gaps, and ethical implications. From the perspective of Maqashid Syariah, these impacts can be directed so that technological progress remains oriented towards the benefit through the principles of hifz al-mal (protection of property), hifz al-nafs (protection of life), and hifz al-'aql (protection of reason). Theoretical Contribution: This research integrates Islamic ethics in understanding the transformation of the digital labor market. Research limitation and implication: This research is limited to literature sources without empirical data support. The implications of this research can form the basis for formulating inclusive and sustainable employment policies.